INVASION OF NOXIOUS ALIEN WEED PARTHENIUM HYSTEROPHORUS L. IN GRAZING LANDS OF LAHORE, PAKISTAN - A. Javaid; S. Shafique; S. Shafique (Journal of Animal and Plant Sciences, 2009)
The present study reports the invasion of noxious, aggressive alien weed parthenium (Parthenium hysterophorous L.) in grazing lands of Lahore, Pakistan. Parthenium was found in all the five studied areas of Lahore exhibiting 100% prevalence. Out of total 53 weed species found in the surveyed areas, only 5 weed species other than parthenium showed 100% prevalence. Parthenium was found to be the second most densely populated weed species with absolute density (AD) of 16.8 and relative density (RD) of 15.59%, the first being the Cynodon dactylon Pers. with AD of 36 and RD of 33.4%. The other densely populated species with AD ranging from 1.5 – 5.78 were Cypreus rotundus L., Croton sparsiflorus Morong, Euphorbia pilulifera L., E. prostrata L., Malvestrum tricuspidatum A. Gray, Brachiaria ramose (L.) Stapf, Dactyloctenium aegyptium Beauv., Digitaria timorensis (Kunth) Balansa, Echinochloa colonum (L.) Link and Eleusine indica Gaertn. All other weed species showed AD below 1.0. The highest coverage was exhibited by C. dactylon (50%) followed by parthenium (30%).
Keywords: aggressive; noxious; parthenium; weed; relative density